ANALYSIS OF TOURIST TRAVEL PATTERNS TOWARD HEALTH CARE FACILITIES: (Case Study of Prambanan Sub-District, Klaten District) - Nida Hanifah; Marta Nilasari Catur Pujianingsih; Dea Handika Pratiwi; Linta Alfi Fahmi; Fathurohim Anhari; Thoriq Albayani (Geosfera Indonesia, 2018)
One of the sectors that are closely related and reasonably determining for the growth and development of the tourism sector is the health sector. The aim of this research was to a) know the affordability of health care facilities from tourism Prambanan and Plaosan Temple, b) to know the travel patterns of tourists headed for healthcare facilities. This research uses qualitative descriptive method by using data collection observation techniques, documentation, and data analysis using network analysis. The network analysis method that used is the closest facility. The results of this research show that a) the affordability of the nearest health service facility from the Plaosan Temple object is Kebondalem Lor Puskesmas which is traveled by 1.7 km distance and takes about 4 minutes from the location of Plaosan Temple, while the closest health service facility from the Prambanan Temple is Prambanan Puskesmas which is taken with distance of 5.3 km and travel time 14 minutes from location of Prambanan Temple. to be known travelers can use private vehicles at tourism Plaosan Temple, because the attractions have a radius of 1.7 km. While on the tourist object of tourism Prambanan Temple can not use private vehicle because the mileage exceeds 3 km, and b) The travel pattern of tourists to health care facilities is categorized good, because the tourists can access health services with the nearest route and adequate facilities. Keywords: Travel Patterns, Health Facilities, Network Analysis ReferencesAnwar, A. (2010). Introduction to Health Administration.Jakarta: Binarupa Aksara.Groenou, M. V., & Tilburg, T. V. (1975). Network Anaysis. Vrije Universitet, Amsterdam, The Netherland.Kuntarto, A., & Purwanto, T. H. (2012). Use of Geographic Information Network Analysis System for Route Planning Tourists in Sleman. Journal of The Earth Indonesia of Vol 1 Number 2, 141.Laksono, A. D., & dkk. (2016). The accessibility of health service in Indonesia. Yogyakarta: KANISIUS PT.Law number. 36 Year 2009 About HealthLaw number. 47 Year 2016 About Health Facilities.Moeleong, L. (2002). Qualitative Research Methods. Bandung: Teens Rosdakarya.Muta'ali, L. (2013). Regional and City Spatial Planning (Tinjauan Normatif-Teknis). Yogyakarta: Badan Penerbit Fakultas Geografi (BPFG) Gadjah Mada University.Narsid, S. (1988). Development Geography. Jakarta: Space.O.Z, T. (1997). Transport Planning and Modeling. Bandung: Institut Teknologi Bandung. Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License